2019
DOI: 10.1111/jtxs.12460
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glycerol on the physicochemical properties of films based on legume protein concentrates: A comparative study

Abstract: The overall goal of this research was to examine the mechanical, water vapor barrier properties and opacity of films prepared using legume protein concentrates (faba bean, pea, lupin, lentil, and soy) as a function of glycerol concentration (50, 75, or 100% [wt/wt]—relative to the protein weight). Overall, tensile strength (TS) decreased with increasing glycerol concentration, whereas tensile elongation (TE) and water vapor permeability (WVP) increased with increasing glycerol concentration. Film opacity was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…Probiotic bacteria are encapsulated with native and modified soy PI, soy and pea protein concentrates, resulting in improved survivability, storage stability, and tolerance in the in vitro gastrointestinal tract conditions (Gharibzahedi & Smith, 2021). Various legume protein concentrates (faba bean, pea, lupin, lentil, and soy) have been used for the edible film formulations by blending with the plasticizer, glycerol (Hopkins et al, 2019), with the developed films exhibiting good mechanical and barrier properties (Bamdad et al, 2006). Saremnezhad et al (2011) prepared flexible edible films from faba bean PI and recommended those edible films to be used for packaging of light sensitive foodstuffs.…”
Section: Legume Proteinsmentioning
confidence: 99%
“…Probiotic bacteria are encapsulated with native and modified soy PI, soy and pea protein concentrates, resulting in improved survivability, storage stability, and tolerance in the in vitro gastrointestinal tract conditions (Gharibzahedi & Smith, 2021). Various legume protein concentrates (faba bean, pea, lupin, lentil, and soy) have been used for the edible film formulations by blending with the plasticizer, glycerol (Hopkins et al, 2019), with the developed films exhibiting good mechanical and barrier properties (Bamdad et al, 2006). Saremnezhad et al (2011) prepared flexible edible films from faba bean PI and recommended those edible films to be used for packaging of light sensitive foodstuffs.…”
Section: Legume Proteinsmentioning
confidence: 99%
“…The obtained results showed that the NSCP films TS and YM were reduced significantly when the GJ increased; whereas, film EB increased significantly until 6% GJ, and remained at almost same value at 8% and 10% GJ. Those film mechanical properties were observed by using glycerol, which is recognized as the most used plasticizer to obtain films, even in protein-or polysaccharide-based films [38,76]. Therefore, we recognized that GJ has plasticizing effect for NSPC film, based on the main ingredients of GJ, which are mainly sugars, well known for plasticizing effects.…”
Section: Film Thickness and Mechanical Propertiesmentioning
confidence: 99%
“…Similar results were observed for alginate [ 18 ], starch [ 20 , 21 ], and chitosan [ 22 ] based films. Similarly, Gly concentration increase resulted in a significant decrease in the tensile strength, whereas the EAB of legume protein-based films increased [ 23 ]. However, Gly addition increased the TS of Eucheuma cottonii waste seaweed biodegradable films [ 24 ].…”
Section: Resultsmentioning
confidence: 99%